ROLE OF PHARMACIST INTERVENTION ON COPD PATIENTS OF SELECTED AREAS IN CHITRADURGA: A KAP STUDY - Mathews, Melvin K; Siddiq, Abubaker; R, Bharathi D (Journal of Biomedical and Pharmaceutical Research, 2019)
Background: Chronic obstructive pulmonary disease (COPD) is preventable and treatable disease state characterized by air flow limitation that is not fully reversible. Severity of the symptoms is increased during exacerbations. Objectives: The purpose of the study is to assess and improve the knowledge regarding COPD among study subjects. Materials and Methods: A Cross-sectional interventional study was carried out among the peoples in selected areas of the Chitradurga city for a period of six months. Result: A total 207 subjects enrolled in the study in that 155 male and 52 females. In our study mean score of post test was more (5.87±1.68) when compare to pre-test (2.63±1.46) which show significant increase in their knowledge after educating them (p=0.000). A total of 207 subjects were enrolled into the study. SPSS Software was used to calculate the statistical estimation. Paired t-test was used to detect the association status of different variables. Conclusion: The relatively good level of COPD awareness needs to be maintained to facilitate future prevention and control of the disease. This study had identified that negative illness perceptions should be targeted, so that they will not avoid patients from seeking for COPD treatment and adhere to it. Key words: Cross sectional study, Knowledge, practice, COPD.